Assessing Training contents, curriculum and process of Agri-entrepreneurship development for farmers (Bangladesh Journal of Agriculture, 2022)
There is a lot of saying about farmers becoming ‘entrepreneurs.’ But what is an agri-entrepreneur and what is agri-entrepreneurship? How can agri-entrepreneurial skills be developed? How do agri-entrepreneurial farmers respond to change their farming enterprise? How can extension workers help farmers to develop agri-entrepreneurial capacity? These questions are still unexplored in Bangladesh. The objectives of this study were to assess the existing agri-entrepreneurship development training manuals for the purpose of identifying better yet unexploited contents and curriculum in facilitating sustainable entrepreneurial skills and attitude of farmers, which will contribute to growth in agribusiness and income for farmers of the country. The methodology included document collection, key informant interview (KII), and literature review and analysis. The managerial skills and entrepreneurial spirit of farmers are essential for agri-entrepreneurship; rural farmers have a high potentiality of agri-entrepreneurship; however, they are facing challenges to gained formal entrepreneurial training and supports, and extension workers must provide demand-driven training and advisory services to enhance agri-entrepreneurship. Investing in agri-entrepreneurship can open a new horizon of agricultural development.Bangladesh J. Agri. 2022, 47(1): 102-112